2020
DOI: 10.1097/anc.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Thermoregulation

Abstract: Background: Premature infants are poor regulators of body temperature and are subjected to environmental factors that can lead to rapid heat loss, leaving them vulnerable to an increased risk of morbidity and mortality from hypothermia. Thermoregulation protocols have proven to increase survival in preterm infants. Purpose: To evaluate a Plan-Do-Study-Act (PDSA) cycle on a previously implemented Golden Hour protocol at a military medical care facility f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
(44 reference statements)
1
8
0
3
Order By: Relevance
“…However, implementing a standardized approach to DR resuscitation of VPIs, such as the "Golden Hour Protocol," has been shown to reduce rates of admission hypothermia and may be beneficial to individual centers seeking to improve outcomes. 23,24 The results of this study are similar to those of previous studies, which reported a significant correlation between admission hypothermia and mortality. A cohort study conducted in Guinea-Bissau found that a body temperature below 34.5 °C significantly increased the risk of infant death by about five times in the first 7 days of life and was associated with an increased mortality rate between 8 and 56 days after birth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, implementing a standardized approach to DR resuscitation of VPIs, such as the "Golden Hour Protocol," has been shown to reduce rates of admission hypothermia and may be beneficial to individual centers seeking to improve outcomes. 23,24 The results of this study are similar to those of previous studies, which reported a significant correlation between admission hypothermia and mortality. A cohort study conducted in Guinea-Bissau found that a body temperature below 34.5 °C significantly increased the risk of infant death by about five times in the first 7 days of life and was associated with an increased mortality rate between 8 and 56 days after birth.…”
Section: Discussionsupporting
confidence: 90%
“…However, implementing a standardized approach to DR resuscitation of VPIs, such as the “Golden Hour Protocol,” has been shown to reduce rates of admission hypothermia and may be beneficial to individual centers seeking to improve outcomes. 23 24…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Because of the complexity of care that needs to be delivered within the Golden Hour, many neonatal units rely on evidence-based bundles of care, based on specific needs of the unit, for example, improving admission temperatures, or reducing rates of bronchopulmonary dysplasia or intraventricular hemorrhage. [12][13][14] Although having the right equipment available is critical to completing a quick and effective admission, emerging research suggests that teamwork may be more important than previously suggested. 5,6,15 It is critical that all members of admission teams understand their role and operate on a shared mental model.…”
Section: Available Knowledgementioning
confidence: 99%
“…Because of the complexity of care that needs to be delivered within the Golden Hour, many neonatal units rely on evidence-based bundles of care, based on specific needs of the unit, for example, improving admission temperatures, or reducing rates of bronchopulmonary dysplasia or intraventricular hemorrhage. 12 14 …”
Section: Available Knowledgementioning
confidence: 99%
“…Hypothermia is one of the common causes of morbidity and mortality in preterm infants. It may directly or indirectly lead to complications such as respiratory disturbances, metabolic derangements such as hypoglycemia, acidosis, renal failure, coagulopathy, and even death [3]. Temperature regulation in preterm infants is much more challenging than in term babies.…”
mentioning
confidence: 99%